CARDIOVASCULAR DISEASES AND CARDIAC CATHETERIZATION: A LITERATURE REVIEW (Fiep Bulletin - online, 2011)
INTRODUCTION: The cardiovascular diseases are the leading causes of morbidity and mortality in developedcountries and in most developing countries and are responsible for high mortality rates. However, the use of a diagnostic method,such as cardiac catheterization, the correct identification of the atherosclerotic process, may be decisive in the prevention ofsevere complications. OBJECTIVES: To identify publications in the Lilacs, Medline and scientific production on cardiovasculardiseases, as well as the advantages and disadvantages of the cardiac catheterization. MATERIAL AND METHOD: A literaturereview of cardiovascular disease, cardiac catheterization, their advantages and disadvantages, raised in the databases ofMedline and Lilacs and publications in the area. RESULTS AND DISCUSSION: The high cost of cardiovascular disease wasdiscussed in 80% of publications. 12 publications have emphasized the advantages disadvantages arising from catheterization.CONCLUSIONS: Most of the publications that involve the cardiovascular addresses issues concerning the high costs of healthcare under such conditions; cardiac catheterization even being considered an evolution of medicine has its advantages anddisadvantages, among which include: the rapid patient recovery and short hospital stay, complications of the access, the use ofcontrast and vascular, respectively.
Keywords: cardiac catheterization and coronary artery disease; nursing